Implementation Of Minister Of Transportation Regulation Number 133 Of 2015 Concerning Periodic Testing Of Motorized Vehicles In Realizing Traffic Safety In The City Of Manado - Anggrainy Claudya Ribka Sangeroki; Petrus Polyando; Rizki Amalia (Sean Institute, 2024)
One of the government's efforts to realize public order and protect the community, especially in realizing traffic safety, as well as minimizing the incidence of traffic accidents is actualized in the policy of periodic testing of motor vehicles. This policy is contained in Minister of Transportation Regulation Number 133 of 2015 concerning Periodic Testing of Motor Vehicles. The aim of this research is to describe the implementation of Minister of Transportation Regulation Number 133 of 2015 concerning Periodic Testing of Motor Vehicles in realizing traffic safety in the City of Manado. This research uses qualitative research methods with a descriptive approach. The data collection techniques used were observation, interviews and documentation. The informants in this research were the Regional Secretary of Manado City, Member of the Manado City DPRD, Head of the Manado City Transportation Service, Head of the Motor Vehicle Testing UPT of the Manado City Transportation Service, Head of the Road Transport Operational Control Section of the Manado City Transportation Service, Staff of the Manado City Transportation Service, Chairman of the Manado City Land Transport Organization, and Motor Vehicle Owner. The results of this research indicate that the implementation of Minister of Transportation Regulation Number 133 of 2015 concerning Periodic Testing of Motor Vehicles in realizing traffic safety in the City of Manado has not gone well as seen from: 1) Communication dimensions (socialization, counseling and coaching) which are less than optimal and less effective carried out, 2) Dimensions of resources (HR and facilities) that have not been supported and are inadequate, 3) Dimensions of bureaucratic structures (SOP and coordination) that have not been effective, 4) Dimensions of disposition (controlling) or supervision that have not been running optimally carried out as inspections , raids, pick-up tests related to periodic testing of motor vehicles.